The Impact of Leadership Support and Communication on Employee Engagement and Working Environment: The Intermediating Role of Performance Management Systems in the UAE Public Sector - Malakmurad, Sameera Abdulrahman; Al-Mekhlafi, Al-Baraa Abdulrahman (International Review of Management and Marketing, 2026)
This study investigates the mechanisms through which leadership behaviours, specifically Leadership Support (LS) and Leadership Communication (LC), influence Employee Engagement (EE) within the administrative context of the UAE Ministry of Education. It specifically examines the dual mediating roles of Performance Management Systems (PMS) and the Working Environment (WE). A quantitative research design was employed, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data from 319 administrative personnel. The study grounded its hypotheses in Social Exchange Theory and Open Systems Communication Theory. Descriptive statistics revealed a highly positive administrative climate (Mean = 4.4). The structural model assessment confirmed that the impact of leadership on engagement is significantly enhanced when filtered through formalized systems. Leadership Communication emerged as the most critical predictor of engagement (Total Effect = 0.500). Critically, mediation analysis demonstrated that PMS and the Working Environment serve as vital structural bridges; LC significantly influences engagement through both PMS (β = 0.149, t = 3.235) and WE (beta = 0.213, t = 4.355). The findings suggest that in hierarchical public sector organizations, leadership intent must be institutionalized through performance management and environmental resources to effectively drive engagement. Importance-Performance Matrix Analysis (IPMA) identifies leadership communication as a high-priority area for strategic development.